Strongyloides, HTLV-1 and small bowel obstruction. Issue 12 (9th December 2019) - Martyn, Emily; Gration, Betty; Subbiah Somasundaram, Chitra; Chiodini, Peter L
Abstract : An 81-year-old Jamaican man who has been resident in the UK for many years presented with one week history of generalised abdominal pain, postprandial vomiting, anorexia, weight loss and abdominal distension. He was managed conservatively for acute small bowel obstruction. Investigations revealed a duodenal stricture. Live Strongyloides stercoralis larvae were observed in stool samples and duodenal biopsy confirmed the presence of the parasite at multiple life cycle stages within the lamina propria. He was diagnosed with Strongyloides hyperinfection with underlying human T-cell lymphotropic virus type 1 and treated with a prolonged course of ivermectin with ongoing monitoring for relapse. This case demonstrates a rare but potentially fatal cause of small bowel obstruction.